(3GdaJhMGJ GdZjHjI aj TQM GdbUjOI GdYbGHjIs - (3YHO GdeLjO GdeUQjs; (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s
(3ChdgG (B:s
(3bGd GdeUfa (B: (3CYde jG CNj Cf gPg GdMceI GdTQjaI hGdYdhe GddWjaI bO UGQJ dHYOgG Yf Ybhd GdNGUI hGdYGeI s
(3BNQgG (B:s
(3hGdahFO GdWjaI GdQhMGfjI GdYXjeI GdLOhi hCMSfgG hCJe GdCaYGd hCcedgG aYdjc HeG fPcQg ajgG hefgG Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B261 - (3U(B276s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs